Control algorithm for an elastic-viscoplastic model to study processes of shock interaction of bodies - V. L. Lapshin; Е. V. Zenkov (Advanced Engineering Research, 2021)
Introduction. In engineering practice, dynamic processes, with the help of which mechanics of interaction of machine components and structural elements are described and studied, are of great importance. These dynamic processes are the cause of large deformations leading to the destruction. The research objective is to develop a more accurate shock simulation algorithm through the controlled transformation of the mechanorheological shock process model from elasticviscous to elastic-viscoplastic.Materials and Methods. Differential equations of the model movement are proposed. The conditions for the transformation of the model during the transition from elastic to plastic deformations, from the stage of loading the model to the stage of unloading under the shock interaction with the surface, are considered. When calculating deformations, the assumption is made that elastic and plastic deformations occur simultaneously from the very onset of the impact. The model functioning method is considered in detail, the algorithm of the model operation is developed, the logic of its functioning is described in detail.Results. To study shock processes, a mechanoreological elastic-viscoplastic model was developed. An important parameter of the model is the force corresponding to the onset of plastic deformation. As a result of the research, a more perfect algorithm was created, and a new computer program was developed to study the shock process using an elasticviscoplastic model with an adjustable elastic-plastic transformation. Discussion and Conclusions. The results obtained can be used to improve the accuracy and reliability of simulation of shock processes in order to further develop the techniques for determining the physical and mechanical characteristics of materials by shock methods. Knowledge of the mechanical characteristics of materials is required when solving various research problems through mathematical modeling of vibration and shock processes. At the same time, an important task is to adapt the design model to the real shock process, for which it is required to develop appropriate methods and techniques.